Estimated glomerular filtration rate for longitudinal follow-up of living kidney donors. Issue 6 (22nd February 2018) - van Londen, Marco; Wijninga, Anthony B; de Vries, Jannieta; Sanders, Jan-Stephan F; de Jong, Margriet F C; Pol, Robert A; Berger, Stefan P; Navis, Gerjan; de Borst, Martin H
ABSTRACT: Background: Living kidney donor safety requires reliable long-term follow-up of renal function after donation. The current study aimed to define the precision and accuracy of post-donation estimated glomerular filtration rate (eGFR) slopes compared with measured GFR (mGFR) slopes. Methods: In 349 donors (age 51 ± 10, 54% female), we analysed eGFR according to the 2009 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, Modification of Diet in Renal Disease (MDRD) and Cockcroft–Gault/body surface area (CG/BSA), creatinine clearance (CrCl) and mGFR ( 125 I-iothalamate) changes from 3 months until 5 years post-donation. Results: Donors had a pre-donation mGFR of 116 ± 23 mL/min, at 3 months post-donation mGFR was 73  ± 14 mL/min and at 5 years it was 79 ± 16 mL/min. Between 3 months and 5 years post-donation, 28% of donors had a declining mGFR (−0.82 ± 0.79 mL/min/year), 47% were stable and 25% had an increasing mGFR. Overall, eGFR equations showed good slope estimates (bias eGFRCKD-EPI 0.13 ± 2.16 mL/min/year, eGFRMDRD 0.19 ± 2.10 mL/min/year, eGFRCG/BSA −0.08 ± 2.06 mL/min/year, CrCl −0.12 ± 4.75 mL/min/year), but in donors with a decreasing mGFR the slope was underestimated (bias eGFRCKD-EPI 1.41 ± 2.03 mL/min/year, eGFRMDRD 1.51 ± 1.96 mL/min/year, eGFRCG/BSA 1.20 ± 1.87 mL/min/year). The CrCl had a high imprecision [bias interquartile range −1.51–3.41 mL/min/year]. Conclusions: All eGFR equations underestimated GFR slopes in donors with a declining GFR between 3 months and 5 years post-donation. This study underlines the value of mGFR in the follow-up of donors with risk of progressive GFR loss.